KAHAW VERSUS NGAHAW: SINONIMI KATA KERJA DALAM KALIMAT IMPERATIF BAHASA BAKUMPAI - Ida Royani (JURNAL BAHASA, SASTRA DAN PEMBELAJARANNYA, 2019)
Abstract Kahaw versus Ngahaw: Sinonimi Verbs In The Imperative Sentence ofBakumpai Language. This study aims to describe the imperative verbs used inBakumpai language command sentences. Command sentences are sentences thatintend to give orders or can also contain a prohibition for someone not to dosomething. The command sentence contains the verb element followed by theobject. For example, in the command sentence: Bring the book! The commandsentence spoken by the speaker contains the hope that the other person will reactor respond, both verbal and nonverbal responses. This study used descriptivequalitative method. The research data were obtained from oral data, namely theinformants and the researchers themselves as native speakers of Bakumpai. Thereare a number of verbs used in Bakumpai language command sentences which aredefinitely different from other language verbs. For example, verbs kahaw andngahaw which mean 'call'. The two verbs are used in Bakumpai languagecommand sentences and are interpreted the same even though the form isdifferent. Apart from the verbs of kahaw and ngahaw, there are other similarimperative verbs. A number of imperative verbs are used in two categories ofcommand sentences, namely (1) a command sentence asking someone to takeaction, and (2) a sentence of disobedience or prohibition. Command sentences inwritten language are marked with an exclamation point (!) At the end of thesentence, and there are auxiliary words that serve to refine utterances such as'pang' and 'my account'. Whereas in spoken language the most obvious marker ofintonation is rising at the beginning. Key words: kahaw versus ngahaw, sinonimi, imperatif, BakumpaiAbstrak Kahaw versus Ngahaw: Sinonimi Kata Kerja dalam Kalimat Imperatif BahasaBakumpai. Penelitian ini bertujuan untuk mendeskripsikan kata kerja imperatifyang digunakan dalam kalimat perintah bahasa Bakumpai. Kalimat perintahadalah kalimat yang bermaksud memberikan perintah atau dapat juga berisilarangan kepada seseorang untuk tidak melakukan sesuatu. Kalimat perintahmengandung unsur kata kerja yang diikuti objek. Misalnya, pada kalimat perintah:Ambilkan buku itu! Kalimat perintah yang dituturkan oleh pembicara berisiharapan agar lawan bicara memberikan reaksi atau tanggapan, baik berupatanggapan verbal maupun nonverbal. Penelitian ini menggunakan metodedeskriptif – kualitatif. Data penelitian diperoleh dari data lisan yaitu informan dan peneliti sendiri sebagai penutur asli bahasa Bakumpai. Ada sejumlah kata kerjayang digunakan dalam kalimat perintah Bahasa Bakumpai yang sudah pastiberbeda dengan kata kerja bahasa lain. Misalnya, kata kerja kahaw dan ngahawyang bermakna ‘panggil’. Kedua kata kerja itu dipakai dalam kalimat perintahbahasa Bakumpai dan dimaknai sama meskipun bentuknya berbeda. Selain katakerja kahaw dan ngahaw, masih ada kata kerja imperatif lain yang serupa.Sejumlah kata kerja imperatif ini dipakai dalam dua kategori kalimat perintah,yakni (1) kalimat perintah meminta seseorang untuk melakukan tindakan, dan (2)kalimat perintah ingkar atau larangan. Kalimat perintah dalam bahasa tulisditandai dengan tanda seru (!) pada akhir kalimat, dan ada kata bantu yangberfungsi memperhalus ucapan seperti ‘pang’ dan ‘akangku’. Sedangkan dalambahasa lisan penanda yang paling jelas adanya pola intonasi yakni naik padabagian awal. Kata-kata kunci: kahaw versus ngahaw, sinonimi, imperatif, Bakumpai